THE EFFECTIVENESS OF USING STORYBIRD TO TEACH DESCRIPTIVE TEXT WRITING TO TENTH GRADE STUDENTS AT SMAN 2 SEKAYAM - Ervina Fitriana; Aunurrahman; Rahayu Meliasari; Heti Susanti (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to examine the effectiveness of using Storybird, a digital storytelling platform, in teaching descriptive text to X-grade students at SMAN 2 Sekayam. The sample consisted of 28 students. A quantitative approach was employed using a pre-experimental one-group pre-test and post-test design. The instrument used was written test that evaluated five aspects: content, organization, vocabulary, grammar, and mechanics. Data were analyzed using SPSS software through the Wilcoxon Signed Rank Test and effect size calculation. The results revealed a significant improvement in students’ writing scores, increasing from a pre-test mean of 37.23 to a post-test mean of 59.55, with a moderate effect size of 0.74. The Wilcoxon Signed Rank Test yielded a p-value of < .001, indicating a statistically significant difference. These findings suggest that Storybird positively influences students’ ability to write descriptive texts, particularly in generating and developing ideas. Keywords: Storybird, Descriptive Text, Writing Skill.